Developing Countries and Monitoring WTO Commitments in Response to the Global Economic Crisis - Bown, Chad P. (2012)
This paper examines the role of the public sector in providing additional information to exporters in developing countries as they seek to monitor and keep open their access to foreign markets by using the rules of the WTO system. It highlights new information generation and dissemination initiatives undertaken by the WTO Secretariat, Global Trade Alert, and the World Bank in response to the global economic crisis of 2008-2009. Given trends in the imposition of new crisis-era trade barriers that these initiatives have identified, the paper describes ways in which the new sources of rich and detailed data may be used to further assist developing country exporters that may lack the capacity to sufficiently monitor their trading interests by relying solely on private resources.